Spatially resolved spectroscopy of alkali metal vapour diffusing inside hollow-core photonic crystal fibres - Häupl, Daniel; Weller, Daniel; Loew, Robert; Joly, Nicolas (New Journal of Physics, 2022)
We present a new type of compact and all-glass based vapour cell integrating hollow-core photonic crystal fibres. The absence of metals, as in a traditional vacuum chamber and the much more compact geometry allows for fast and homogeneous heating. As a consequence we can fill the fibres on much faster timescales, ranging from minutes to hours. Additionally the all-glass design ensures optical access along the fibre. This allows live monitoring of the diffusion of rubidium atoms inside the hollow-core by measuring the frequency-dependent fluorescence from the atoms. The atomic density is numerically retrieved using a five-level system of Bloch-equations.
CRIS-Team WoS Importer:2022-11-25